The Case for S2: The Potential Benefits of the S2 Subunit of the SARS-CoV-2 Spike Protein as an Immunogen in Fighting the COVID-19 Pandemic - Shah, Priyanka; Canziani, Gabriela A.; Carter, Erik P.; Chaiken, Irwin (Frontiers in Immunology, 2021)
As COVID-19 cases continue to rise, it is imperative to learn more about antibodies and T-cells produced against the causative virus, SARS-CoV-2, in order to guide the rapid development of therapies and vaccines. While much of the current antibody and vaccine research focuses on the receptor-binding domain of S1, a less-recognized opportunity is to harness the potential benefits of the more conserved S2 subunit. Similarities between the spike proteins of both SARS-CoV-2 and HIV-1 warrant exploring S2. Possible benefits of employing S2 in therapies and vaccines include the structural conservation of S2, extant cross-reactive neutralizing antibodies in populations (due to prior exposure to common cold coronaviruses), the steric neutralization potential of antibodies against S2, and the stronger memory B-cell and T-cell responses. More research is necessary on the effect of glycans on the accessibility and stability of S2, SARS-CoV-2 mutants that may affect infectivity, the neutralization potential of antibodies produced by memory B-cells, cross-reactive T-cell responses, antibody-dependent enhancement, and antigen competition. This perspective aims to highlight the evidence for the potential advantages of using S2 as a target of therapy or vaccine design.